Mariette’s Newly Released Documents and the Chronology of the Apis Bulls - Porter, Robert (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
The Louvre Museum recently placed online Mariette’s notebooks from the mid 19 th century which include information on the find-spots of stelae from the Lesser Vaults of the Memphis Serapeum, the underground tomb complex of the Apis bulls at Saqqara. Some of these stelae name the reigning pharaoh and/or give dates for the bulls. The tombs had been ransacked but it seems that enough stelae remained close to their original positions to help determine the approximate location of each bull burial, a subject which has long been debated. Analysis of Mariette’s documents suggests a greater overlap between Dynasties 22 and 25 than is generally accepted.